Finding allowance distribution for root and connecting rod necks of crankshaft forging according to coordinate measurements - D. T. Safarov; A. V. Chekh (Омский научный вестник)
The article analyzes various ways to ensure the geometric parameters of forgings in the processes of hot volumetric stamping. The fact of high efficiency of coordinate measurements of geometric parameters of forgings has been established to ensure the identification of negative production factors affecting the geometric accuracy of forgings manufacturing. The designs of common control devices and measurement schemes of geometric parameters of the crankshaft forging do not allow performing coordinate measurements of the crankshaft forging in shop conditions. The coordinate scheme, the design of the control device and the method of determining the size of the parameters of the allowance distribution along the root and connecting rod necks of the crankshaft are considered. On the basis of the methodology given in the article for determining the parameters of the allowance distribution, a technique for controlling the geometric accuracy of hot volumetric stamping has been developed, the accuracy of controlling the output parameters of the geometric accuracy of forgings of crankshafts of heavy-duty vehicles has been improved.